Comparison of coronary computed tomography angiography-derived vs invasive fractional flow reserve assessment: meta-analysis with subgroup evaluation of intermediate stenosis - Baumann, Stefan; Hetjens, Svetlana; Becher, Tobias; Loßnitzer, Dirk; Lehmann, Ralf; Akın, Ibrahim; Borggrefe, Martin; Lang, Siegfried (Academic radiology, 2016)
Rationale and Objectives - Invasive coronary angiography (ICA) with fractional flow reserve (FFR) assessment is the reference standard for the detection of hemodynamically relevant coronary lesions. We have investigated whether coronary computed tomography angiography (cCTA)-derived FFR (fractional flow reserve from coronary computed tomographic angiography [CT-FFR]) measurement improves diagnostic accuracy over cCTA. - Methods and Results - A literature search was performed for studies comparing invasive FFR, cCTA, and CT-FFR. The analysis included three prospective multicenter trials and two retrospective single-center studies; a total of 765 patients and 1306 vessels were included in the meta-analysis. Compared to invasive FFR on a per-lesion basis, CT-FFR reached a pooled sensitivity, specificity, positive predictive value, and negative predictive value of 83.7% (95% confidence interval [CI]: 78.1-89.3), 74.7% (95% CI: 52.2-97.1), 64.8% (95% CI: 52.1-77.5), and 90.1% (95% CI: 80.8-99.3) compared to 84.6% (95% CI: 78.1-91.1), 49.7% (95% CI: 31.1-68.4), 39.0% (95% CI: 28.0-50.1), and 87.3% (95% CI: 72.5-100.0) for cCTA alone. In 634 vessels with intermediate stenosis (30%-70%), sensitivity, specificity, positive predictive value, and negative predictive value were 81.4% (95% CI: 70.4-92.9), 71.7% (95% CI: 54.5-89.0), 59.4% (95% CI: 35.5-83.4), and 89.9% (95% CI: 85.0-94.7) compared to 90.2% (95% CI: 80.6-99.9), 35.4% (95% CI: 23.5-47.3), 50.7% (95% CI: 30.6-70.8), and 82.5% (95% CI: 64.5-100.0) for cCTA alone. The summary area under the receiver operating characteristic curve of CT-FFR was superior to cCTA alone on a per-vessel (0.90 [95% CI: 0.82-0.98] vs 0.74 [95% CI: 0.63-0.86]; P = .0047) and for intermediate stenoses (0.76 [95% CI: 0.65-0.88] vs 0.57 [95% CI: 0.49-0.66]; P = .0027). - Conclusion - CT-FFR significantly improves specificity without noticeably altering the sensitivity of cCTA with invasive FFR as a reference standard for the detection of hemodynamically relevant stenosis.
Gesehen am 18.04.2019
Available online 14 September 2016